Real-time quantification of osteoclastic resorptive activity by electric cell-substrate impedance sensing - Jansen, Ineke D.C.; van Velzen, Thijs; de Vries, Teun J.; Szulcek, Robert; van Loon, Jack J. W. A. (Frontiers in Cell and Developmental Biology, 2022)
In several diseases, bone resorption by osteoclasts is dysregulated. Thus far, no simple technique for real-time measurement of resorption is available. Here, we introduce an impedimetric bioassay for real-time monitoring of resorption by making use of electrical insulating properties of the resorbable substrate calcium phosphate. Different chemicals stimuli were applied to (pre)osteoclasts cultured on a layer of calcium phosphate in multi-well plates containing electrodes. By this, osteoclast activity can be measured continuously over days and effects of stimulating or inhibiting factors can be quantified. When cells were cultured in the presence of an inflammatory factor such as IL-1β the resorptive activity started earlier. The measured decline in resistance was higher at culture day 5 compared to cultures with M-CSF or M-CSF+RANKL (M-CSF norm. resistance=1, M-CSF+RANKL=0.7, M-CSF+RANKL+ IL-1β=0.5). However, at day 11 this difference had nearly disappeared. Likewise, bisphosphonates were shown to inhibit osteoclastic activity. Our findings illustrate the importance of real-time monitoring; wherefore this method has high potential for the study of osteoclast resorptive activity in the context of osteoclast function and diseases, but also could find application in high throughput drug-testing studies.